Designing and Implementing the Model of Public Assessment of Social and Cultural Progress in Universities - Gholamreza Khaje Sarvi; Alireza Aliahmadi; Alireza Moeini; Mostafa Dezfooli (Taḥqīqāt-i Farhangī-i Īrān)
Implementing Investigations, analyzes and performance measurements in special and qualitative social/cultural arena in our country, needs local and special methodologies. Thus the aim of present article is investigating these issues: the concept of culture, classification of cultural organizations in Islamic Republic of Iran, the Pyramidal structure of cultural hierarchy, the process of development and mutual influences of institutions, reviewing related literature of policy making in cultural issues, compatibility of strategies to existing realities in cultural performance structure, double division in measures and analyzing and elaborating suggested measures in elaborating weighting model and assessment method and investigating progress measures by focusing on Islamic-Iranian pattern of progress and investigating the effects of implementing this pattern plus weighting method and using related measures and studying some university cases which are implemented in three phases in universities and high education centers overall the country. This research has shown a linear model by considering weighting coefficients.